Analisis Konsumsi dan Produksi Energi Kebun Hidroponik Tenaga Surya di Desa Lenek Lombok Timur : Analisis Konsumsi dan Produksi Energi Kebun Hidroponik Tenaga Surya di Desa Lenek Lombok Timur - Alimin; Muhammad Nurswal Isnani; Yuliani Hasni; Rizkia Rahmawati; Muji Juherwin (Institut Riset dan Publikasi Indonesia, 2026)
The utilization of solar energy in hydroponic systems offers a potential solution to reduce dependence on conventional electricity and lower operational costs. This study aims to analyze the balance between energy consumption and production in a solar-powered hydroponic farm located in Lenek Daya Village, East Lombok Regency. The system consists of two 80 Wp solar panels, a 4 × 4.2 W water pump, a light sensor, and a 12 V 100 Ah battery for energy storage. The research method includes daily measurement of energy production and consumption over one month, as well as 10-minute interval monitoring for three consecutive days to capture short-term energy dynamics. The results show that daily energy production ranges from 200 to 350 Wh, while energy consumption remains relatively stable between 100 and 200 Wh. The production profile follows a diurnal pattern, with peak power occurring between 11:30 and 14:00. Overall, the solar panels sufficiently meet the system’s energy requirements, even generating a surplus under clear weather conditions. However, weather fluctuations significantly affect daily production, highlighting the important role of energy storage in ensuring continuous operation. This study concludes that the implementation of solar-powered hydroponic systems is feasible and efficient, supporting sustainable agricultural operations in rural areas.